2021
DOI: 10.1537/ase.2012132
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomes from the initial Jomon period: new insights into the genetic history of the Japanese archipelago

Abstract: Starting 16000 years ago, the Neolithic lifestyle known as the Jomon culture spread across the Japanese archipelago. Although extensively studied by archaeology and physical anthropology, little is known about the genetic characteristics of the Jomon people. Here, we report the entire mitogenome and partial nuclear genome of skeletal remains from the initial Jomon period that were excavated from the Higashimyo shell midden site at Saga City, Kyushu Island, Japan. This is the first genome analysis of the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…This finding broadly supports a core tenet of the dual structure hypothesis for the population history of Japan, wherein migrants from mainland Asia, likely through the Korean peninsula, moved to the Japanese archipelago starting 3,000 years ago, and mixed with indigenous Jōmon populations [86,95]. Adachi et al also estimated that present-day Korean and Ulchi populations in northeast Asia show 5%-8% Jōmon ancestry [64]. Furthermore, in f4-statistics, Jōmon individuals show connections to present-day Austronesians and 8,000-7,000-year-old individuals from coastal southern East Asia and Siberia [85,86].…”
Section: Ancestry and Admixture In Southern East Asia Southeast Asia And The Japanese Archipelagosupporting
confidence: 54%
See 2 more Smart Citations
“…This finding broadly supports a core tenet of the dual structure hypothesis for the population history of Japan, wherein migrants from mainland Asia, likely through the Korean peninsula, moved to the Japanese archipelago starting 3,000 years ago, and mixed with indigenous Jōmon populations [86,95]. Adachi et al also estimated that present-day Korean and Ulchi populations in northeast Asia show 5%-8% Jōmon ancestry [64]. Furthermore, in f4-statistics, Jōmon individuals show connections to present-day Austronesians and 8,000-7,000-year-old individuals from coastal southern East Asia and Siberia [85,86].…”
Section: Ancestry and Admixture In Southern East Asia Southeast Asia And The Japanese Archipelagosupporting
confidence: 54%
“…These ancient individuals were associated with the Jōmon period of Japan, the first cultural period found in the archaeological record dating from 16,000 to 2,800 years ago. They were originally from the northern reaches of Hokkaido [83], the central and northern regions of Honshu [63,81,84,85], and the southern island of Kyushu [64]. These Jōmon individuals consistently cluster together in a PCA and show high genetic similarity to each other distinct from that found in other Asian populations; their associated ancestry is denoted here as Jōmon ancestry (Box 2, Figure 2).…”
Section: Early Lineages Of Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…,Saitou and Jinam (2017), andJinam et al (2021a) is compatible with these datasets Adachi et al (2021). reported the first Jomon genome data from the Higashimyo shell midden site, Kyushu, dated c. 8000 years ago.…”
supporting
confidence: 58%
“…reported the first Jomon genome data from the Higashimyo shell midden site, Kyushu, dated c. 8000 years ago. Their principal-components analysis shows that the genome of Hokkaido Jomon people reported byKanzawa-Kiriyama et al (2019) and that of Kyushu Jomon reported byAdachi et al (2021) are very similar, suggesting striking homogeneity of the Jomon people over a long time.…”
mentioning
confidence: 95%